Os vínculos entre educador e educando no ensino médio: experiências de ética e reconhecimento em escolas públicas - Meucci, Arthur (2016)
This thesis develops and defends the notion that teaching-learning relationships in the classroom environment encompass ethical conflicts in the search for mutual recognition. It argues that the hurdles faced by high school teachers are directly related to deep-rooted conflicts inherent in students’ pursuit of recognition. The study investigated both the teaching strategies of experienced teachers, considered to be highly effective by their peers, as well as strategies used by inexperienced teachers, for a comparative analysis. It is based on Axel Honneths’s philosophical and social contributions on the moral grammar of social conflicts in the struggle for recognition within the classroom environment, as well as the psychoanalytical theories of Donald Winnicot related to the nature of the Self and its processes of emotional development and attachment. During this study, qualitative research was conducted in the context of two state schools in São Paulo, in areas of both high and low economic growth, over a period of two years. As regards methodology, an adaptation of the Depth Hermeneutics formulated by John Thompson was employed during three phases. The first phase gathered documents and interviews with community members, in order to collect information related to the cultural and historical contexts of the schools and interviewees. The second phase took place during a six month-period of classes and included ethnographic reports of two teachers with over 10 years of experience, two teachers beginning their careers and one teacher with 5 years of experience and on probation period. Finally, the third phase of the research consisted of gathering together the study field surveys and the theoretical approach to make interpretations and reinterpretations of the observed phenomena. The result showed that the majority of conflicts between students and teachers occur due to struggles for recognition rather than relationships between “quality class” and “behavioral problems”. Results show that creative gestures in the teaching-learning environment derive from a potential space that allows a bond of trust between students and their teachers.